2021
DOI: 10.1016/j.heliyon.2021.e06245
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic inhibition of enterocytic starch digestion enzymes and glucose transporters for managing type 2 diabetes may be reduced in food systems

Abstract: With the current global surge in diabetes cases, there is a growing interest in slowing and managing diabetes and its effects. While there are medications that can be used, they have adverse side effects such as hypoglycemia and weight gain. To overcome these problems, bioactive compounds commonly found in fruits, vegetables and cereal grains are used to slow starch digestion and transport of simple sugars across the intestinal epithelia thereby reducing plasma blood glucose spike. These effects are achieved t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 94 publications
0
19
0
Order By: Relevance
“…Similarly, when these extracts of phenolic compounds are incorporated into food systems, they can interact with other biopolymers (carbohydrates, proteins, lipids) in the food matrix. This leads to lower inhibition of digestion and/or glucose transporters, compared to when they are ingested as an extract or in pure compound forms without additional matrix biomolecules, as often observed in most in vitro cell systems [77].…”
Section: Phytochemical Compounds: Structure Food Sources Bioavailabil...mentioning
confidence: 99%
“…Similarly, when these extracts of phenolic compounds are incorporated into food systems, they can interact with other biopolymers (carbohydrates, proteins, lipids) in the food matrix. This leads to lower inhibition of digestion and/or glucose transporters, compared to when they are ingested as an extract or in pure compound forms without additional matrix biomolecules, as often observed in most in vitro cell systems [77].…”
Section: Phytochemical Compounds: Structure Food Sources Bioavailabil...mentioning
confidence: 99%
“…In this context, RS can act as a substrate for microbial fermentation in the large intestine [42] by supplying an energy source and fermentative products, such as short-chain fatty acids (SCFAs) in their anionic forms, in such a way RS is able to modulate microbial growth and could influence colonic health (Figure 2). On this basis, RS is believed to be a prebiotic and to influence the GI of foods favoring a lower intestinal absorption of glucose, even in the presence of polyphenols that in turn inhibits enterocytic starch digestion enzymes [43] It has been reported that the extended lack of dietary fiber can lead to irreversible changes in the gut microbiota composition and elicit gut dysbiosis, even impairing gut inflammatory mediators, thereby inducing several bowel diseases [44].…”
Section: Resistant Starch In Human Nutritional Intervention Studies: Gi and Impact On Inflammation And Gut Microbiomementioning
confidence: 99%
“…Moreover, some flavonoids showed a higher affinity with the pasta, as with quercetin-3-O-glucuronide, kaempferol-O-glucuronide, apigenin-O-glucuronide and 3,5-O-dicaffeoylquinic acid, present in C. intybus as also the phenylpropanoids present in P. coronopus, when compared with the other phenolic compounds identified in the plant extracts. This aspect could be due to the interaction of chemical components of the egg-pasta such as the gluten as already reported or the starch present in the wheat flour, able to link with the glycosidic phenolic compounds, inhibiting the release of the glucose in the human body and making the phenolic compounds more bioavailable for intestinal absorption (Ayua et al, 2021;Coe, Clegg, Armengol, & Ryan, 2013;Törrönen et al, 2013). These results are confirmed by the antioxidant activity assays, showing higher inhibition of lipid peroxidation and antihemolytic activity of plant extract enriched pasta than the control pasta, as reported in the next paragraph and in Table 1.…”
Section: Phenolic Compounds Fingerprintingmentioning
confidence: 95%